Pengaruh Pendidikan Kesehatan Dan Model Peer Group Terhadap Perilaku Ibu Melakukan Deteksi Dini Kanker Serviks - Iana Aulia Andari; Sulastri Sulastri (Jurnal Berita Ilmu Keperawatan, 2017)
Cervical cancer is a type of cancer that affects most women over the age of 18 or women of childbearing age. This cancer is the second deadliest cancer in the world after breast cancer (IARC, 2010).The anatomic location of the neck of the uterus or cervix is located inside the woman's body causes difficult to see signs appear physiologically. On the other hand the lack of knowledge of a woman neighbor and how to prevent cervical cancer and early detection is also one of the factors that affect a woman who had cervical cancer entered into the phase of the advanced stage to lead to death. In this study, the authors will take a single location within a community member in it all of a woman aged 30-60 years as many as 86 people are in association branches located in the district Aisyiyah Kartasura, Pucangan village. Researchers will divide the group into two groups with the different treatment given, namely the control group were 43 persons with health education is given through lectures from researchers and experiment groups given 43 models of a peer group with a sampling multistage random sampling technique . The results of this study showed there is significant health education with behavioral models of the Peer Group on Mother did Cervical Cancer Early Detection between the experimental group with the control group. The behavior of a mother with stats early detection of cervical cancer both in the experimental group on the post-test either Behaviour there were 27 ( 62.8 %), the behavior is quite 5 people ( 11.6 % ) and poor as many as 11 people ( 25.6 % ). whereas the behavior of the control group at post-test behavioral changes of 34 ( 79.1 % ) respondents was less supportive reduced to 5 respondents (11.6 % ) who behave fairly but found the existence of respondents who support either as many as 4 people ( 9, 3 % ).